Yoga Practice on Reducing Menstrual Pain Intensity (Dysmenorrhea) in Adolescent Girls: Literature Review - Nuring Dwi Hareni; Anggia Astuti; Zainal Abidin (KHD Production, 2023)
Most women experience severe pain problems during menstruation, usually called dysmenorrhea. Yoga practice can reduce body, mind, and psychic tension, reduce pain, and release endorphins to increase the response of the parasympathetic nerves which causes vasodilation of blood vessels throughout the body and uterus, and increases uterine blood flow thereby reducing the intensity of dysmenorrhea. This study aimed to determine the effect of yoga practice on reducing menstrual pain intensity (dysmenorrhea) in adolescent girls. This study used a literature review design using 3 databases, namely PubMed, Science Direct, and Google Scholar. The results showed that in the study, the exercises used were yoga with a percentage of 100% using yoga practice interventions. Yoga practice was done within 30-60 minutes per session with a period of 1-3 times a week. Menstrual pain in adolescents who were given yoga practice in the journal experienced a decrease in pain intensity with p = 0.05. Yoga can stimulate the body to release endorphins and enkephalins, inhibiting pain. Yoga is performed by relaxing the endometrial muscles when contractions and ischemia occur due to increased prostaglandin levels, which will cause vasodilation of blood vessels and cause blood flow to experience spasms and spasms ischemia and then reduce pain. Yoga will change the pattern of pain acceptance towards calming the body and will gradually recover from pain disorders. Yoga practice can be an alternative to reduce the intensity of menstrual pain in adolescent girls.